Cardiovascular outcomes and safety with antidiabetic drugs - Aldossari, Khaled K. (International Journal of Health Sciences, 2018)
Type 2 diabetes is a debilitating disease that impacts the life expectancy, quality of life, and health of an individual. Cardiovascular disease (CVD) is a common diabetes-associated complication and a principal cause for death in diabetic patients. This review aims to investigate and summarize the effect of Type 2 diabetes mellitus (T2DM) medications on CVD issues. A comprehensive literature review mainly from level 1 evidence was performed. Thirty-seven articles were extracted from Google Scholar, ScienceDirect, ProQuest, and PubMed Database using a combination of keywords. The findings suggest that different glucose-lowering agents have been tested for their efficacy and safety in T2DM with CVD. Some of the recent trials such as the “United Kingdom Prospective Diabetes Study,” “Empagliflozin (EMPA) Cardiovascular (CV) Outcome Event Trial in T2DM Patients-Removing Excess Glucose” (EMPA-REG OUTCOME), “Liraglutide Effect and Action in Diabetes: Evaluation of CV Outcome Results,” and “Trial to Evaluate CV and Other Long-term Outcomes with Semaglutide in Subjects with Type 2 Diabetes” (SUSTAIN6) have shed important light on this vital clinical concern, thus demonstrating a convincing effect of liraglutide, semaglutide, and EMPA on CVD outcomes, while metformin is thought to be the first-line optimal oral agent to manage Type 2 diabetics. Some classes of drugs demonstrate CV protection, some of them may be a result of a class effect, and some differences might be based on the population enrolled individually. Most of the trials failed to show a significant benefit with regard to mortality and morbidity in spite of intensive glycemic control. This study, therefore, enabled us to develop a guide of potential antidiabetic medication that can influence or promote CV health. Health professionals in future should weigh the CV risk against possible advantages while prescribing antidiabetic medications.